The diagnostic value of circulating tumor cells for lung cancer: A systematic review and meta-analysis. Issue 12 (March 2019) - Ye, Yun; Li, Su-Liang; Wang, Jian-Jun; Liu, Bing
Abstract: Background: Circulating tumor cells (CTCs) have become a potential diagnostic tumor marker and have the potential for wide clinical applications. However, the diagnostic parameters vary among previous studies. A systematic review of the literature and meta-analysis were conducted to assess the diagnostic value of CTCs for lung cancer. Methods: Eligible studies were searched in PubMed, Medline, Cochrane Library, and Embase databases. The included studies assessed the diagnostic value of CTCs in patients with lung cancer up to September 30, 2018. A total of 1601 patients in 8 studies were included in the meta-analysis. We calculated the pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and area under the curve (AUC) to investigate the diagnostic value of CTCs for lung cancer. STATA version 12.0 and Meta-DiSc version 1.4 software were used to analyze the data. Results: The pooled sensitivity was 0.75 (95% CI: 0.73–0.78), the specificity was 0.89 (95% CI: 0.86–0.92), the PLR was 6.29 (95% CI: 3.98–9.96), and the NLR was 0.24 (95% CI: 0.14–0.42). Furthermore, the pooled DOR of CTCs for lung cancer was 27.73 (95% CI: 12.99–59.23). The summarized area under the ROC curve was 0.93 (95% CI: 0.90–0.95). The meta-regression analysis suggested that the heterogeneity was mainly attributed to the experimental methods. The results of the clinical diagnosis efficiency show that the diagnostic efficiency has increased significantly by testing CTCs for diagnosing lung cancer. Conclusion: The results of this meta-analysis suggest that CTCs are associated with a high diagnostic value for lung cancer. These findings require large-scale prospective studies to verify and evaluate the diagnostic value in the future.